The Impact of Component Modification of “Double Bottom Filter” Recirculation System to Concentration of Ammonia in Water and Survival Rate at Rearing Media of Blue Devil Fish (Chrysiptera cyanea) - F. Sahetapy, Jacqueline M; Louhenapessy, Daniel G; Riry, Elna C (Aquacultura Indonesiana, 2016)
Blue devil (Chrysiptera cyanea), blue damselfish, is a variety of marine ornamental fish. In rearing ornamental fish, water quality management is required to maintain the optimal condition of water quality. Filtration and recirculation are proven as preeminent ways to manage the optimal condition of water quality in aquarium as the vessel for rearing ornamental fish. Simple recirculation system double bottom filter was applied in this research with treatments of components modification of the system. The objective of the research was to identify the concentration of ammonia in rearing media of blue devil (C. cyanea) using recirculation system double bottom filter with several modification components. The treatments are i.e. (1) no recirculation/aeration only (treatment A), (2) system with components of sand and dacron (treatment B), (3) sand and sponge (treatment C). The result showed that the ammonia concentration in system A (control) was 0.890 mg/L, system B (sand and dacron) was 0.129 mg/L, and system C (sand and sponge) was 0.7 mg/L. The highest value of survival rate was in system B (components sand and dacron) which valued 90%. As the conclusion, component sand and dacron in recirculation system double bottom filter provided better performance in reducing ammonia in rearing media of blue devil (C. cyanea) which also confirmed with the survival rate value.